Upaya Meningkatkan Kemampuan Membaca Permulaan Siswa melalui Media Big Book - Maria Ulfa; Putri Nabilah Yuliana Yusuf; Romanti Sirait (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
The success of learning in the classroom must begin with good reading skills. With skilled reading, students will be able to understand and master all the material provided by the teacher. To be skilled at reading students must start from mastering the ability to read the beginning. The purpose of this study was to improve students' ability to read simple sentences through big book media in 28 grade I students at SD Negeri Babelan Kota 08, Bekasi, West Java, Odd Semester 2022-2023 Academic Year. This research is a Classroom Action Research (CAR) with the Kemmis and McTaggart models with 4 stages, namely plan, act, observe, and reflect. Data collection techniques in this study were preliminary reading tests, observations, interviews, field notes, and documentation. This research was conducted in 3 cycles. After applying the big book media can improve students' initial reading skills. The results of the pre-action presentation of learning success were 21.43%, in the first cycle the presentation of learning success was 50%, in the second cycle the presentation of learning success was 64.28%, and the presentation of learning success reached 71.42% in cycle III. Based on the results of this study, using big book media can improve students' initial reading skills.